Upcycling of carrot discards into prebiotics (fructooligosaccharides) as high value food ingredients - Guerra, Laureana (2023)
A great amount of carrots is discarded daily in the word because they do not meet the quality standards imposed by consumer market. The aim of this work was to evaluate the feasibility of using carrot discards as substrate of solid-state fermentation to produce β-fructofuranosidase by Aspergillus niger and its subsequent use to catalyze the synthesis of fructooligosaccharides (prebiotics) using carrot juice. Results indicated that carrot bagasse has adequate nutrients for the growth of A. niger, but supplementation with a source of nitrogen is required to obtain a high production of β-fructofuranosidase (90.82 U/mL). Maximum specific activity (251 U/mg) was obtained after 3 days of fermentation at 30 ºC, using an inoculum of 106 conidia/ mL. β-fructofuranosidase was successfully used to synthesize fructooligosaccharides using carrot juice as substrate, raising the possibility for future development of a natural functional beverage. Tweetable abstract: A great amount of carrots is discarded daily. This paper evaluates the use of carrot bagasse to produce β-fructofuranosidase and its subsequent application in carrot juice to produce a natural beverage with prebiotics.